Hydrocarbon chain-length dependence of solvation dynamics in alcohol-based deep eutectic solvents: a two-dimensional infrared spectroscopic investigation - Chatterjee, Srijan; Ghosh, Deborin; Haldar, Tapas; Deb, Pranab; Sakpal, Sushil S.; Deshmukh, Samadhan H.; Kashid, Somnath M.; Bagchi, Sayan (Journal of Physical Chemistry B, 2019)
Deep eutectic solvents (DESs) have gained popularity in recent years as an environmentally benign, inexpensive alternative to organic solvents for diverse applications in chemistry and biology. Among them, alcohol-based DESs serve as useful media in various applications due to their significantly low viscosity as compared to other DESs. Despite their importance as media, little is known how their solvation dynamics change as a function of the hydrocarbon chain length of the alcohol constituent. In order to obtain insights into the chain-length dependence of the solvation dynamics, we have performed two-dimensional infrared spectroscopy on three alcohol-based DESs by systematically varying the hydrocarbon chain length. The results reveal that the solvent dynamics slows down monotonically with an increase in the chain length. This increase in the dynamic timescales also shows a strong correlation with the concomitant increase in the viscosity of DESs. In addition, we have performed molecular dynamics simulations to compare with the experimental results, thereby testing the capacity of simulations to determine the amplitudes and timescales of the structural fluctuations on fast timescales under thermal equilibrium conditions.

Curious case of aqueous warfarin: structural isomers or distinct excited states? - Sakpal, Sushil S.; Ghosh, Deborin; Manae, Meghna A.; Hazra, Anirban; Bagchi, Sayan (Journal of Physical Chemistry B, 2021)
Warfarin is a potent anti-coagulant drug and is on the World Health Organization's List of Essential Medicines. Additionally, it displays fluorescence enhancement upon binding to human serum albumin, making warfarin a prototype fluorescent probe in biology. Despite its biological significance, the current structural assignment of warfarin in aqueous solution is based on indirect evidence in organic solvents. Warfarin is known to exist in different isomeric forms-open-chain, hemiketal, and anionic forms-based on the solvent and pH. Moreover, warfarin displays a dual absorption feature in several solvents, which has been employed to study the ring-chain isomerism between its open-chain and hemiketal isomers. In this study, our pH-dependent experiments on warfarin and structurally constrained warfarin derivatives in aqueous solution demonstrate that the structural assignment of warfarin solely on the basis of its absorption spectrum is erroneous. Using a combination of steady-state and time-resolved spectroscopic experiments, along with quantum chemical calculations, we assign the observed dual absorption to two distinct pi ->pi* transitions in the 4-hydroxycoumarin moiety of warfarin. Furthermore, we unambiguously identify the isomeric form of warfarin that binds to human serum albumin in aqueous buffer.

Evidence of an nN(amide) → π*Ar interaction in N-Alkyl-N,N′-diacylhydrazines - Deka, Jugal Kishore Rai; Sahariah, Biswajit; Sakpal, Sushil S.; Bar, Arun Kumar; Bagchi, Sayan; Sarma, Bani Kanta (Organic letters, 2021)
1,2-Dibenzoyl-1-tert-butylhydrazine (RH-5849) and related N-alkyl-N,N′-diacylhydrazines are environmentally benign insect growth regulators. Herein, we show that an unusual n<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">N(amide) → π*<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">Ar interaction mediated by a hydrazide amide nitrogen atom plays a crucial role in stabilizing their biologically active trans–cis (t–c) rotameric conformations. We provide NMR and IR spectroscopic evidence for the presence of these interactions, which is also supported by X-ray crystallographic and computational studies.

Stabilization of Azapeptides by N-amide center dot center dot center dot H-N-amide Hydrogen Bonds - Baruah, Kalpita; Sahariah, Biswajit; Sakpal, Sushil S.; Deka, Jugal Kishore Rai; Bar, Arun Kumar; Bagchi, Sayan; Sarma, Bani Kanta (Organic Letters, 2021)
An unusual N-amide center dot center dot center dot H-Namide hydrogen bond (HB) was previously proposed to stabilize the azapeptide beta-turns. Herein we provide experimental evidence for the N-amide center dot center dot center dot H-Namide HB and show that this HB endows a stabilization of 1-3 kcal.mol(-1) and enforces the trans-cis-trans (t-c-t) and cis-cis-trans (c-c-t) amide bond conformations in azapeptides and N-methyl-azapeptides, respectively. Our results indicate that these N-amide center dot center dot center dot H-Namide HBs can have stabilizing contributions even in short azapeptides that cannot fold to form beta-turns.

Transition of a deep eutectic solution to aqueous solution: a dynamical perspective of the dissolved solute - Sakpal, Sushil S.; Deshmukh, Samadhan H.; Chatterjee, Srijan; Ghosh, Deborin; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2021)
Disruption of the deep eutectic solvent (DES) nanostructure around the dissolved solute upon addition of water is investigated by polarization-selective two-dimensional infrared spectroscopy and molecular dynamics simulations. The heterogeneous DES nanostructure around the solute is partially retained up to 41 wt % of added water, although water molecules are gradually incorporated in the solute's solvation shell even at lower hydration levels. Beyond 41 wt %, the solute is observed to be preferentially solvated by water. This composition denotes the upper hydration limit of the deep eutectic solvent above which the solute senses an aqueous solvation environment. Interestingly, our results indicate that the transition from a deep eutectic solvation environment to an aqueous one around the dissolved solute can happen at a hydration level lower than that reported for the ``water in DES'' to ``DES in water'' transition.

Association-dissociation dynamics of ionic electrolytes in low dielectric medium - Ghosh, Deborin; Sakpal, Sushil S.; Chatterjee, Srijan; Deshmukh, Samadhan H.; Kwon, Hyejin; Kim, Yung Sam; Bagchi, Sayan (Journal of Physical Chemistry B, 2022)
Ionic electrolytes are known to form various complexes which exist in dynamic equilibrium in a low dielectric medium. However, structural characterization of these complexes has always posed a great challenge to the scientific community. An additional challenge is the estimation of the dynamic association-dissociation time scales (lifetime of the complexes), which are key to the fundamental understanding of ion transport. In this work, we have used a combination of infrared absorption spectroscopy, two-dimensional infrared spectroscopy, molecular dynamics simulations, and density functional theory calculations to characterize the various ion complexes formed by the thiocyanate-based ionic electrolytes as a function of different cations in a low dielectric medium. Our results demonstrate that thiocyanate is an excellent vibrational reporter of the heterogeneous ion complexes undergoing association-dissociation dynamics. We find that the ionic electrolytes exist as contact ion pairs, dimers, and clusters in a low dielectric medium. The relative ratios of the various ion complexes are sensitive to the cations. In addition to the interactions between the thiocyanate anion and the countercation, the solute-solvent interactions drive the dynamic equilibrium. We have estimated the association-dissociation dynamics time scales from two-dimensional infrared spectroscopy. The exchange time scale involving the cluster is faster than that between a dimer and an ion pair. Moreover, we find that the dynamic equilibrium between the cluster and another ion complex is correlated to the solvent fluctuations.